The Influence of Aerobic Exercise on Gross Motor Development Achievements in Children Aged 5-6 Years at St Antonius Kindergarten 2 Medan Academic Year 2023/2024 - Ivena Gultom; Simatupang, Dorlince; Damanik, Suri Handayani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research was to determine the effect of aerobic exercise on the gross motor development of children aged 5-6 years at TK ST Antonius 2 Medan. This type of research is experimental research with an Only Post-test control Group Design. The population in the study was 6 class B. So the sample in this study was Kindergarten B children, totaling 13 people in the experimental class and 13 people in the control class. This research data was obtained using observation techniques using instrument sheets. The data analysis technique uses non-parametric statistics with the Mann Whitney test. The test results show that aerobic exercise has a significant influence on the development of children's gross motor skills with the criteria for testing the hypothesis if H0 is accepted Ucount < Utabel, H0 is rejected if Ucount > Utabel. The result of the hypothesis test was 2.5385 < 4.4, it was proven that H0 was rejected, meaning that there was a significant increase in gross motor development by being given aerobic exercise in the experimental class compared to the control class which was not given aerobic exercise but rather rhythmic exercise. Thus, it can be concluded that there is a significant influence of aerobic exercise on the gross motor development of children aged 5-6 years at TK ST Antonius 2 Medan FY 2022/2023.